Utilization of chemically treated cashew-nut shell as potential adsorbent for removal of Pb(II) ions from aqueous solution - Kamchai Nuithitikul (Nature Portfolio, 2020)
Abstract In this study, cashew nut shells (CNS), waste from a cashew nut processing factory, have been used as an adsorbent for Pb(II) ions in water. Treatments of CNS with 1 M of H2SO4, HNO3, and NaOH solutions were performed to modify their surfaces and improve their adsorption capacities. Characterization of untreated and chemical-treated CNS was carried out using nitrogen adsorption isotherm, elemental (CHN) analysis, Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDX). In the study of Pb(II) removal, various models of adsorption kinetics and isotherms were evaluated against the experimental data. The results showed that H2SO4-treated CNS exhibited the highest adsorption capacity. The chemical treatment removes impurities, alters the surface functional groups and improves specific surface areas and pore volumes of native CNS significantly. Surface adsorption and intra-particle diffusion steps were found to substantially affect the overall adsorption process of Pb(II) on H2SO4-treated CNS. Owing to its easy preparation and comparable adsorption capacity, H2SO4-treated CNS has the potential to be developed as a low-cost adsorbent for the removal of Pb(II) from contaminated water.